Significantly enhanced thermal conductivity of polymer composites via establishing double-percolated expanded graphite/multi-layer graphene hybrid filler network - Liu, Chao; Wu, Wei; Drummer, Dietmar; Wang, Yi; Chen, Qiming; Liu, Xingrong; Schneider, Kevin (European Polymer Journal, 2021)
Utilization of hybrid fillers with high thermal conductivity enhancement (TCE) efficiency is an effective method for the large-scale fabrication of polymeric thermal interface materials (TIMs) with exceptional thermal conductivity. Herein, we report the thermally conductive properties of thermoplastic urethane (TPU) composites incorporated with expanded graphite (EG) and multi-layer graphene (MLG). The effect of percolation behavior of EG/MLG hybrid fillers on the thermal conductivity is systematically revealed. It is found that the high-loading TPU composite with 20 wt% EG and 10 wt% MLG reveals an exceptional thermal conductivity of 8.52 Wm(-1)K(-1), which corresponds to a TCE of 3450% compared to that (0.24 Wm(-1) K-1) of pure TPU matrix. Notably, the TCE per 1 wt% filler reaches a substantial value of 115%. The thermally conductive mechanism is proposed based on morphology and thermal contact resistance analyses. Moreover, the application of such TPU composites in thermal management of light-emitting diode lamps is exhibited, and the effectiveness is further verified through finite element simulation. Our results shed light on the significant thermal synergy between EG and MLG and demonstrate their application potential in high-performance TIMs.
CRIS-Team WoS Importer:2021-10-29